The Analysis of well cuttings for lithological characterization of ‘T’ Sandstone Reservoir from Napo Basal Formation of Early Cretaceous to north of the Oriente Basin (Revista Científica Ciencias Naturales y Ambientales, 2018)
The Lithological Unit ‘T’ Sandstone of Napo Basal Formation from Early Cretaceous of Napo Group has been considered as a second objective on wells drilling. The ‘T’ Sandstone has been divided in two parts for specifics purposes: Main ‘T’ Sandstone and Glauconitic ‘T’ Sandstone. This current work degree was developed to know the lithological characteristics of ‘T’ Sandstone, as well as its structural and petrophysical properties in a north area of the Oriente Basin. Well cuttings, electrical logs and lithological logs from eight wells were used for it. The Upper ‘T’ Sandstone presents interbedded sandstone and shale electrofacies type with high values of Gamma Ray (GR), low Resistivity and poor Porosity; besides, it is characterized to be glauconitic. The Lower ‘T’ Sandstone presents Kaolin minerals accessories and sandstone electrofacies type with low values of GR, medium-high Resistivity and good Porosity; besides, the lower ‘T’ Sandstone has better evidence of hydrocarbons than upper ‘T’ Sandstone. The Lithological Unit ‘T’ Sandstone has a left flank of an anticlinal fold (¿?) with north-south direction and dip west, the thickness increase to east and net sand thickness increase to west.
Keywords: electrofacies; glauconitic; lithological logs